Biomechanical analysis and clinical observation of 3D-printed acetabular prosthesis for the acetabular reconstruction of total hip arthroplasty in Crowe III hip dysplasia - Liu, Yuchen; Wang, Fuyang; Ying, Jiawei; Xu, Minghao; Wei, Yuan; Li, Junlei; Xie, Hui; Zhao, Dewei; Cheng, Liangliang (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: This study aimed to evaluate the biomechanical effectiveness of 3D printed Integrated Acetabular Prosthesis (IAP) and Modular Acetabular Prosthesis (MAP) in reconstructing the acetabulum for patients with Crowe III Developmental Dysplasia of the Hip (DDH). The results of this study can provide a theoretical foundation for the treatment of Crowe III DDH in Total Hip Arthroplasty (THA). Methods: Finite element (FE) analysis models were created to reconstruct Crowe III DDH acetabular defects using IAP and MAP. The contact stress and relative micromotion between the acetabular prosthesis and the host bone were analyzed by gradually loading in three increments (210 N, 2100 N, and 4200 N). In addition, five patients with Crowe III DDH who underwent IAP acetabular reconstruction were observed. Results: At the same load, the peak values of IAP contact stress and relative micromotion were lower than those of MAP acetabular reconstruction. Under jogging load, MAP metal augment's peak stress exceeded porous tantalum yield strength, and the risk of prosthesis fracture was higher. The peak stress in the bone interface in contact with MAP during walking and jogging was higher than that of cancellous bone, while that of IAP was higher than that of cancellous bone only under jogging load, so the risk of MAP cancellous bone failure was greater. Under jogging load, the relative micromotion of MAP reconstruction acetabular implant was 45.2 μm, which was not conducive to bone growth, while under three different loads, the relative micromotion of IAP acetabular implant was 1.5-11.2 μm, all <40 μm, which was beneficial to bone growth. Five patients with IAP acetabular reconstruction were followed up for (11.8±3.4) months, and the Harris score of the last follow-up was (85.4±5.5). The imaging results showed good stability of all prostheses with no adverse conditions observed. Conclusion: Compared with acetabular reconstruction with MAP, IAP prosthesis had a lower risk of loosening and fracture and a better long-term stability. The application of IAP was an ideal acetabular reconstruction method for Crowe III DDH.